A Feasibility study on the Melano LPG Anti-leak Safety Device - Agbayani, Carlo; Duque, Ricci; Lainez, Leon; Regalado, John Michael (College of Engineering, 1999)
The Melano LPG Anti-Leak Safety Device is a product of Filipino ingenuity. Invented by a former employee of the Department of Science and Technology, Mr. Arquilio Y. Melano Sr., the Anti-Leak Safety Device is designed such that when any gas leak is detected, the device will automatically shut off the flow of gas preventing any accidental fires or explosions from happening. Adaptable to all kinds of LPG tanks in the market, the Melano is completely serviceable and all of its parts are replaceable. It is because of the product's safety function and overall features that the proponents of the study chose the Melano LPG Anti-Leak Safety Device as their product for a feasibility study. At the moment, the inventory produces the Safety Device in small factory in Pasig, and his product is manufactured in small quantities. The invention is available in very select places, primarily at inventors' bazaars and exhibits, and the inventor's office in Pateros, Metro Manila. Presently, the Anti-Leak Safety Device does not cater to any particular share of the market of which it is classified. The group, by aid of the conduction of a thorough feasibility study, aims to determine if production of larger quantities of the Safety Device to make it available to a much wider market could be possible and advantageous to both the inventor and buying public. In the Market Study, the target market was first identified. The Melano LPG Anti-Gas Leak Safety Device will be sold to the LPG using households belonging to income levels A, B, & C located in the National Capital Region. From a supply and demand forecast, it was determined that the number of units to be sold are 32,723 units for year 2000; 36,549 units for year 2001; 42,105 units for year 2002, 47,598 units for year 2003; and 53;148 units for 2004. The yearly market share are 4.80%, 5.44% 6.09%, 6.64% and 7.31% respectively. In the Technical Study, it was decided that the product will be produced by manufacturing the main brass stem sub-assembly and subcontracting the other parts. A total of 21 workers will be hired. It was determined that lathe, drilling, tapping, threading, and buffing machines need to be purchased. A suitable plant site was located along Sumulong Hi-way. The total project cost was computed at P44,098,648.72. In the Organizational Study, it was determined that the corporate form of ownership is the most suitable for the Melano Project. A total of 43 employees ranging from managers to workers are required by the organization. In the Financial Study, it was discovered that the investment can be recovered in 1.85 years. The internal rate of return was computed at 37.71% which was way above the 20% MARR which was set. Finally, in the Social Profitability Analysis, it was discovered that the following benefits are generated: Contributions to citizens through income of employees; contributions to the national government through corporate and income taxes, contributions to the local government through municipal fees; and contributions to other industries that supply input. The only drawback is that U.S. dollars will exit the country due to the importation of an imported raw material. though proven feasible by the study conducted, the group solemnly hopes for the success of the actual launching Melano LPG Anti-Leak Safety Device. The proponents of the study wishes that this paper would aid the inventor, Mr. Aquilio Melano, in starting the safety device project. Agbayani, Duque, Lainez and Regalado truly believe in this invention, and we hope it to be a household name someday.